Shared Medical Appointments and Mindfulness for Type 2 Diabetes—A Mixed-Methods Feasibility Study - Ee, Carolyn; de Courten, Barbora; Avard, Nicole; de Manincor, Michael; Al-Dabbas, Mahmoud A.; Hao, Jie; McBride, Kate; Dubois, Shamieka; White, Rhiannon Lee; Fleming, Catharine; Egger, Garry; Blair, Angela; et al. (Frontiers in Endocrinology, 2020)
Introduction Type 2 Diabetes (T2DM) is a major health concern with significant personal and healthcare system costs. There is growing interest in using Shared Medical Appointments (SMAs) for management of T2DM. We hypothesize that adding mindfulness to SMAs may be beneficial. This study aimed to assess the feasibility and acceptability of SMAs with mindfulness for T2DM within primary care in Australia. Materials and Methods We conducted a single-blind randomized controlled feasibility study of SMAs within primary care for people with T2DM living in Western Sydney, Australia. People with T2DM, age 21 years and over, with HbA1c > 6.5% or fasting glucose >7.00 mmol/L within the past three months were eligible to enroll. The intervention group attended six two-hour programmed SMAs (pSMAs) which were held fortnightly. SMAs included a structured education program and mindfulness component. The control group received usual care from their healthcare providers. We collected quantitative and qualitative data on acceptability as well as glycemic control (glycated hemoglobin and continuous glucose monitoring), lipids, anthropometric measures, blood pressure, self-reported psychological outcomes, quality of life and diet, and physical activity (using an ActiGraph accelerometer). Results Over a two-month period, we enrolled 18 participants (10 females, eight males) aged 58 years (standard deviation 9.8). We had 94.4% retention. All participants in the intervention group completed at least four pSMAs. Participants reported that attending pSMAs had been a positive experience that allowed them to accept their diagnosis and empowered them to make changes, which led to beneficial effects including weight loss and better glycemic control. Four pSMA participants found the mindfulness component helpful while two did not. All of the seven participants who contributed to qualitative evaluation reported improved psychosocial wellbeing and found the group setting beneficial. There was a significant difference in total cholesterol levels at 12 weeks between groups (3.86 mmol/L in intervention group vs 4.15 mmol/L in the control group; p=0.025) as well as pain intensity levels as measured by the PROMIS-29 (2.11 vs 2.38; p=0.034). Conclusion pSMAs are feasible and acceptable to people with T2DM and may result in clinical improvement. A follow-up fully-powered randomized controlled trial is warranted.